CONSTRAINTS AND LOYALTY OF THE PARTICIPANTS IN RECREATIONAL DANCING ACTIVITIES - Goulimaris, Dimitris; Darginidou, Lemonia; Genti, Maria (International Journal of Research -GRANTHAALAYAH, 2018)
The aim of this work was to examine the factorial validity of the «leisure constraints scale» by Alexandris and Carroll (1997a) and the investigation of the relationship between the constraining factors of attendance and the participants’ loyalty to leisure dancing activities. The sample of the study was 318 adults who participated in traditional dancing classes organized by cultural associations. The «leisure constraint scale» (Alexandris & Carroll, 1997a) and a conversion of the «loyalty» subscale was used for the investigation of the constraining factors and loyalty as suggested by Zeithaml, Berry and Parasuraman (1996). The data supported the factor structure and the internal consistency of the leisure constraints scale. It was also found that there is a reverse relation of loyalty with five factors of the leisure constraints scale. Generally, it appears that the participants experience the constraining factors of attendance to dancing activities with low intensity.